Analisis potensi air di waduk Sengguruh dan Waduk Wonorejo sebagai PLTA didaerah DAS Brantas: Analisis Potensi Air di Waduk Sengguruh dan Waduk Wonorejo sebagai PLTA di Daerah DAS Brantas - Lailatul, Nur; Sudartik, Sudartik; Yushardi, Yushardi (J-Eltrik, 2024)
The water energy potential found in the Sengguruh and Wonorejo reservoirs serves as a source for Hydroelectric Power Plants (PLTA) located in the Brantas River Basin (DAS Brantas). The river flow has significant potential to be used as a source of electricity generation. The Brantas River possesses considerable potential for the development of Micro-Hydro Power Plants. The Weir and Flume method, which relates to threshold levels, average power, and water discharge, is used. Discharge is calculated based on the water level above the weir or within a narrow channel. At the Sengguruh PLTA, the inflow water discharge produced is 1.57 m³/s. Meanwhile, at the Wonorejo PLTA, the river inflow discharge calculated using the F.J. Mock method ranges from 0.94 m³/s to 16.99 m³/s, with a dependable discharge of 1.833 m³/s. It is therefore concluded that the electrical energy potential between the two reservoirs is greater at the Sengguruh PLTA